2012
DOI: 10.1177/1059840512454546
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Adolescents

Abstract: One of every 10 adolescents in the United States has asthma. Adolescents who lack asthma control are at increased risk for severe asthma episodes and death. The National Heart, Lung, and Blood Institute 2007 asthma guidelines and research studies indicated that school nurses are instrumental in assisting adolescents to monitor their asthma, learn asthma self-management skills, and improve health outcomes. This integrative review examines the research from 2005 to 2011 to identify strategies for school nurses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Poor asthma control among this age group is associated with high morbidity and mortality (17,18,11). Akinbami et al (17) showed a higher asthma mortality rate among adolescents by approximately 1.5 times compared with younger children.…”
Section: Introductionmentioning
confidence: 99%
“…Poor asthma control among this age group is associated with high morbidity and mortality (17,18,11). Akinbami et al (17) showed a higher asthma mortality rate among adolescents by approximately 1.5 times compared with younger children.…”
Section: Introductionmentioning
confidence: 99%